The formation of paraffin wax crystal in flow - Abdul Kadir, Abdul Aziz; Ismail, Issham; Hamid, Mohd. Fauzi (Inst. of Postgraduate Studies and Research, University of Malaya., 1998)
The flow of crude oil from oil reservoir to the surface is controlled by the pressure difference between the subsurface pressure and wellhead pressure at the platform. The pressure drop is also required to pump the crude oil from the platform to the inland processing plant. A significant amount of heavy paraffin components may solidify to form needle-like crystals as the flow temperature reaches the temperature of supercritical fluid. The drop of temperature is due to heat losses to the surrounding and low initial operation temperature. The crystallisation temperature is measured via the Differential Scanning Calorimeter. The Scanning Calorimetry method provides the initial indication of phases transition at simulated heat loss at isobaric condition. The result was correlated to flow properties such as the pour point and fluid rheology.